Disseminated Cryptococcosis in an Immunocompetent Patient: A Case Report - S. Suchitha; C. S. Sheeladevi; R. Sunila; G. V. Manjunath (Hindawi Limited, 2012)
Cryptococcus neoformans is ubiquitous encapsulated yeast found throughout the world. It predominantly causes significant infections in immunocompromised individuals, of which 80-90% occur in people with human immunodeficiency virus (HIV) infection. Disseminated cryptococcal infection is uncommon and almost always occurs in HIV-infected patients. Disseminated disease, especially noncutaneous cryptococcal abscess in immunocompetent hosts, is exceedingly rare. We report a case of disseminated cryptococcosis with soft tissue, pulmonary, and cerebral involvement in an otherwise healthy immunocompetent patient initially diagnosed by fine needle aspiration cytology (FNAC).